Enhanced rate capability and cycling stability of Li1.2-xNaxMn0.54Co0.13Ni0.13O2. (1st April 2016) - Yang, Chaofan; Zhang, Xiaosong; Huang, Junjie; Ao, Peng; Zhang, Gang
Highlights: A new confinement method was used to prepare Na + -doped Li1.2 Mn0.54 Co0.13 Ni0.13 O2 . The initial charge-discharge can be about 90% in Na + doped Li1.2 Mn0.54 Co0.13 Ni0.13 O2 . Rate capability can be improved greatly by sodium doping. Abstract: Li1.2-x Nax Mn0.54 Co0.13 Ni0.13 O2 with nano size is synthesized with a confinement method. Li1.2-x Nax Mn0.54 Co0.13 Ni0.13 O2 (x = 0.05, 0.10 and 0.20) presents enhanced initial charge-discharge efficiency, rate capability and cycling stability in comparison with Li1.2 Mn0.54 Co0.13 Ni0.13 O2 . At 0.1C (25 mA g −1 ), the initial charge-discharge efficiency is increased from 76% of Li1.2 Mn0.54 Co0.13 Ni0.13 O2 to 90% of Li1.1 Na0.1 Mn0.54 Co0.13 Ni0.13 O2 ; and the capacity retention in the 20 th cycle versus the initial cycle is improved from 31% for Li1.2 Mn0.54 Co0.13 Ni0.13 O2 to 88% for Li1.1 Na0.1 Mn0.54 Co0.13 Ni0.13 O2 ; at 500 mA g −1, Li1.1 Na0.1 Mn0.54 Co0.13 Ni0.13 O2 has a discharge capacity of 128 mAh g −1, while the Na-free sample Li1.2 Mn0.54 Co0.13 Ni0.13 O2 only delivers a lower discharge capacity of 54 mAh g −1 . The superior electrochemical performance of Li1.2-x Nax Mn0.54 Co0.13 Ni0.13 O2 (x = 0.05, 0.1 and 0.2) is mainly due to sodium doping, which can enlarge the interslab distance and stabilize the crystal structure.